Robotics as an integration subject in the computer science university studies. The experience of the University of Almeria - Manuela Berenguel Soria; Francisco Rodríguez Díaz; José Carlos Moreno Úbeda; José Luis Guzmán Sánchez; Ramón González Sánchez (Ediciones Universidad de Salamanca, 2012)
This work presents a global view of the role of robotics in computer science studies, mainly in university degrees. The main motivation of the use of robotics in these studies deals with the following issues: robotics permits to put in practice many computer science fundamental topics, it is a multidisciplinary area which allows to complete the basic knowledge of any computer science student, it facilitates the practice and learning of basic competences of any engineer (for instance, teamwork), and there is a wide market looking for people with robotics knowledge. These ideas are discussed from our own experience in the University of Almeria acquired through the studies of Computer Science Technical Engineering, Computer Science Engineering, Computer Science Degree and Computer Science Postgraduate.